Variations of Nutrient Foramen of Femur and its Clinical Implications - Shrestha, Pragya; Mansur, Dil Islam; Mehta, Dilip Kumar; Shrestha, Sheprala; Shrestha, Anupama (Journal of Lumbini Medical College, 2019)
Introduction: Nutrient foramen is the largest opening on the shaft of the femur that conveys nutrient artery into the marrow cavity. Knowledge on locations of nutrient foramina is essential during surgical procedures as well as to rule out if the fracture line passes through the foramina. The purpose of the study was to determine the number and position of nutrient foramina in relation to length and topography of the femur. Methods: The study model was descriptive, cross-sectional study that included 151 femurs (71 right and 80 left side). The total number, location, and direction of nutrient foramina were investigated. Total length of femur and distance of foramen from the proximal end was measured with the 500mm 20" Digital Vernier Nib Jaw Caliper Metric/ Imperial Machine-DRO and finally Foraminal Index was calculated. Results: The analysis revealed 119(78.81%) of the femurs with single nutrient foramen, 31(20.52%) with double and 1(0.67%) with triple nutrient foramina. Foraminal Index II was found in 74(86.05%) on right side and 90(91.84%) on left side. The most common location of nutrient foramen was the medial lip of linea aspera (n= 77, 41.85%). All of the foramina were directed towards the proximal end. Conclusion: The present study has reported the majority of nutrient foramina located in the middle third of femur along the linea aspera. Thus, linea aspera should not be stripped off during surgical procedures to avoid damage to the nutrient arteries.